Calibration accuracy of RCS measurements in free space - Wickramasinghe, Pathiraja; Balleri, Alessio (Institute of Electrical and Electronics Engineers (IEEE), 2025)
When investigating Radar Cross Section (RCS) of targets, it is essential to establish confidence in the experimental calibration data. In this paper, experiments are presented which were carried out to determine the calibration accuracy achieved in performing free space target RCS measurements in the radar lab at Cranfield University. Calibration data were collected in the X-band (between 8.5 GHz and 12 GHz) using four off-the-shelf non-calibrated metallic spheres of different diameter: 30 mm, 38 mm, 80 mm and 100 mm. The results indicate an accuracy of less than ±2 dBm2 for the spheres measured on a styrofoam stand and with a Signal to Noise Ratio (SNR) of at least 40 dB for all spheres.
Keywords: Radar Cross Section; RCS Calibration